2003
DOI: 10.1515/cclm.2003.016
|View full text |Cite
|
Sign up to set email alerts
|

A New Modification of the Chiron ACS Assay for Total Prostate-Specific Antigen Achieves Equimolar Response Characteristics and Improves the Detection of Prostate Cancer

Abstract: Nonequimolar-response assays for prostate-specific antigen (PSA) are criticized for overestimating total PSA in some men without prostate cancer (PCA), and underestimating total PSA in some men with PCA. We recently studied three nonequimolar-response PSA assays that had undergone modifications. While two of the studied assays achieved equimolar-response characteristics with improved areas under receiver operating characteristic (ROC) curves (AUC), the modification of the Chiron ACS PSA assay (ACS PSA2, Chiron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Although the simulations were carried out under the assumption that all PSA assays would use the same assay method, the estimated rates can be applied to the number of tests carried out with a particular assay to estimate the numbers of false-positive and -negative recommendations that it would produce. The results of this study are consistent with two previous reports that showed that the use of an equimolar assay can reduce the number of patients having an unnecessary biopsy by up to 10% (10,11 ). Moreover, it has been shown that reported estimates of diagnostic ability are dependent on assay choice (17 ); thus, combining results from different assays can make generalizations difficult (18 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the simulations were carried out under the assumption that all PSA assays would use the same assay method, the estimated rates can be applied to the number of tests carried out with a particular assay to estimate the numbers of false-positive and -negative recommendations that it would produce. The results of this study are consistent with two previous reports that showed that the use of an equimolar assay can reduce the number of patients having an unnecessary biopsy by up to 10% (10,11 ). Moreover, it has been shown that reported estimates of diagnostic ability are dependent on assay choice (17 ); thus, combining results from different assays can make generalizations difficult (18 ).…”
Section: Discussionsupporting
confidence: 92%
“…The clinical relevance of using an equimolar assay for tPSA remains controversial (9 ), although two recent studies (10,11 ) have shown the superior diagnostic ability of equimolar response assays in differentiating between benign prostatic hyperplasia and prostate cancer. However, there has been no investigation on the impact of assays that are either nonequimolar or biased (i.e., not numerically calibrated to the International Standards) on the decision to recommend a patient to undergo a prostate biopsy for cancer detection.…”
mentioning
confidence: 99%
“…However, almost all of the aforementioned methods are either only for the detection of TPSA or only for the measurement of FPSA, which usually results in unmatched F/T ratios. [18][19][20] Furthermore, two separated measurements would unavoidably result in bigger errors than the simultaneous assay because of different effects of pipetting error in each analyte that could be eliminated using the simultaneous assay.…”
Section: Introductionmentioning
confidence: 99%
“…Nonuniform assay calibration and nonequimolar detection of the various PSA forms are possible reasons for these discordant results (1)(2)(3)(4)(5)(6). PSA reference materials compiled by the WHO and equimolarresponse assays were developed to adjust PSA calibration (7)(8)(9)(10)(11)(12), but since their introduction, several manufacturers (e.g., Beckman Coulter, Roche Diagnostics, and Diagnostic Products Corp.) have changed their assay platforms, and the few available comparison studies, with limited numbers of assays and small numbers of samples, have not fully characterized the current situation (13,14 ). Therefore, focusing on the clinically important tPSA range up to 10 g/L, we evaluated and characterized 5 frequently used fPSA and tPSA assay combinations with regard to the interchangeability of PSA values among the assays, their equimolar characteristics, and the diagnostic accuracy, estimated by ROC analyses, particularly of the percentage ratios of fPSA to tPSA (%fPSA).…”
mentioning
confidence: 99%